Effect of Al and Ta Impurities on Si Adsorption on (001) and (111) Surfaces of B1-TiN - Yury M. Koroteev; Leonid A. Svyatkin; Sergey O. Ognev; Vyacheslav M. Silkin (Crystals)
Nowadays, the application of protective multicomponent coatings based on hard metal nitrides is increasingly used to increase the resistance of structures and tools to wear, corrosion, and oxidation. In the present work, the multicomponent system Ti-Al-Ta-Si-N is studied, which has high hardness and crack resistance combined with thermal stability and oxidation resistance. The process of formation of the nanocrystalline structure of the coating during its deposition on materials plays a key role in the optimization of these properties. The nanocrystalline structure of the coating is formed due to Si impurity, which is poorly soluble in the Ti1−x−yAlxTayN system based on B1-TiN and segregates mainly along grain boundaries, forming grain boundary amorphous phases of SizN type. In order to find the optimal composition of multicomponent coatings with improved physical and mechanical properties, it is necessary to understand the peculiarities of interaction of Si impurity with the surface of B1-TiN phase in the presence of Al and Ta substitutional impurities. In the present work, with the help of first-principles calculations of electronic and atomic structure of (001) and (111) surfaces of the Ti1−x−yAlxTayN system with adsorbed Si atom and the interatomic bond study apparatus based on the calculation of a crystal orbital Hamilton population and a crystal orbital bond index, the nature of the bonds between adsorbed Si and the N, Ti, Al, and Ta atoms of the Ti1−x−yAlxTayN surface system has been studied. It was found that the binding energy of Si with the Ti1−x−yAlxTayN surface system can be both higher and lower than the binding energy of its bonding with the surface of the binary TiN compound depending on the position of the Al and Ta substitution atoms in the surface layers. The Si bonding with the atoms of the Ti1−x−yAlxTayN surface is ionic–covalent in nature. It is shown that the Si-Ta interaction has the highest degree of covalency and strength, and the Si-Al interaction is predominantly ionic in most cases considered and is weaker than the Si-Ti and Si-N bonds. Impurity atoms of Al or Ta have very little effect on the Si-Ti and Si-N bonds due to the local nature of the bonds in the Ti1−x−yAlxTayN surface system with adsorbed silicon atoms.